Concealed Around-the-Ear EEG Captures Cognitive Processing in a Visual Simon Task - Pacharra, Marlene; Debener, Stefan; Wascher, Edmund (Frontiers in Human Neuroscience, 2017)
In theory, miniaturized EEG systems such as around-the-ear electrode arrays (cEEGrids) enable mobile monitoring in a variety of real life situations without interfering with the natural setting. However, the research benefit of such cEEGrid recordings critically depends on their validity. To investigate whether visual and motor processing are reflected in the cEEGrid-EEG, a direct comparison of EEG that was concurrently recorded with the cEEGrids and with a high-density cap setup was conducted. Thirteen participants performed a classic Simon task in which letters were presented laterally and a lateralized choice response was executed. N1, P1 and P300 event-related potential waveforms were extracted from cEEGrid-EEG: They were found to be strongly correlated with corresponding waveforms extracted from cap-EEG but with lower signal strength and lower signal-to-noise-ratio. Event-related lateralizations (ERLs) recorded at posterior scalp sites were well reflected in middle cEEGrid pairs. Moreover, the effect size of the Simon correspondence effect on the extracted ERLs was similar between the two systems. However, lateralizations at central cap sites were less well reflected in the cEEGrid-EEG indicating a difficulty in capturing motor response preparation and execution. These results show that well-described visual and cognitive ERPs and ERLs can be measured using the cEEGrids, while motor-related cortical potentials are not well captured. The study further demonstrates the potential and possible limitations of unobtrusive cEEGrid-EEG recordings.